Family Life Stress, Coping, and Mental Health among Vietnamese Marriage Migrant Women in South Korea: A Mixed Methods Study - Phuong Thao, Nguyen Thi (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Vietnamese marriage migrant women experience multiple stressors associated with married life in South Korea. While there are a number of studies investigating acculturative stress, relatively little work has examined family life stress and its harmful effect on mental health among these marriage migrant women. The purpose of this paper is to explore the impact of family life stress on depression and the mediating roles of some personal coping resources (self-esteem and specific coping behaviors) on this relationship among a sample of Vietnamese marriage migrant women living in South Korea. The study utilizes a mixed methods design. A quantitative survey is completed by 301 Vietnamese migrant wives with a mean age of 29 years (SD=5.49). Qualitative interviews are conducted with five Vietnamese migrant wives and analyzed using thematic analysis. The findings indicate that family life stress is positively related to depression, both directly and indirectly through low self-esteem and greater use of avoidant coping. The study provides several implications for social work research and practice.Received: 1st March 2016; Reviesed: 29th March 2016; Accepted:10thApril 2016